Advancing the Circular Economy in Public Sector Organisations - Klein, Natacha (2022)
Circular economy (CE) is a concept that is gaining attention as an approach to help accelerate the transition towards sustainability. Research has focused on the adoption of CE practices in the business sector while the adoption within public sector organisations has been relatively overlooked. Examining CE adoption in the public sector through the perceptive of employees is crucial because of their expertise in the organisation where they work. The main aim of this study is to identify what public employees perceive as suitable CE practices for their organisations and their critical role in implementation. As the adoption of CE practices is influenced by social and material configurations, this research has taken a case study approach, focused on the Portuguese Central Public Administration. Semi-structured interviews were conducted with public employees working on CE and sustainability issues, and a complementary analysis was undertaken of governmental reports and legislative documents. The results show that public employees view the existence and potential of CE practices mainly in the area of public procurement but also in resource efficiency and optimisation, dematerialisation and in practices related to the R-hierarchy including reduce and reuse. Both technical-oriented practices aimed to achieve traditional resource efficiency, and human-centred practices targeted at reducing consumption and sharing resources have been identified. This research provides insights into how a specific group of stakeholders envisions CE activities for their sector. Identification of practices for central public sector has the potential to assist decision-makers in the process of defining priorities for CE planning, implementation and monitoring. This study focusing on CE practices in central public sector organisations contributes to the calls for an inclusion of human/socially-based practices centred around consumption reduction, sharing and dematerialisation activities to enhance the transformative and innovative potential of CE.